2003
DOI: 10.1016/s0014-5793(03)00894-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation and a free radical scavenger suppress angiotensin II‐induced downregulation of klotho, an anti‐aging gene, in rat

Abstract: Administration of angiotensin II to rats decreases renal expression of klotho, an aging-related gene, and also causes abnormal iron deposition in renal cells. Here we have examined the e¡ects of iron overload and iron chelation on renal expression of klotho in untreated rats and rats treated with angiotensin II. Administration of iron^dextran caused a downregulation of klotho expression, and iron chelation suppressed the angiotensin II-induced downregulation of this gene. In addition, a free radical scavenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 16 publications
(20 reference statements)
5
71
0
2
Order By: Relevance
“…10 We found that Ang II-induced aberrant iron homeostasis may have modulatory effects on the extent of urinary protein excretion 10 and on the expression of genes that have relation to anti-aging 14 and fibrogenesis. 11 However, notably, in situ hybridization showed that the localization of upregulation of TGF-␤1 mRNA and deposition of iron were found to occur in different renal tubular cells.…”
Section: Discussionmentioning
confidence: 90%
“…10 We found that Ang II-induced aberrant iron homeostasis may have modulatory effects on the extent of urinary protein excretion 10 and on the expression of genes that have relation to anti-aging 14 and fibrogenesis. 11 However, notably, in situ hybridization showed that the localization of upregulation of TGF-␤1 mRNA and deposition of iron were found to occur in different renal tubular cells.…”
Section: Discussionmentioning
confidence: 90%
“…The rat TGF-␤1 cDNA probe was a kind gift from Dr. Shiow-Shih Tang (Harvard Medical School, Massachusetts General Hospital, Boston, Massachusetts) and Dr. John S. D. Chan (Centre Hospitalier de l'Université de Montréal-Hôtel-Dieu, Mon-treal, Quebec, Canada). Rat collagen type I cDNA was obtained by subcloning the RT-PCR product using rat kidney mRNA and validated by DNA sequencing using the dideoxyribonucleotide sequencing method, as described previously (27). These cDNA probes were labeled with [␣-32 P]dCTP (Amersham Life Sciences, Piscataway, NJ) using commercial kits (Nippon Gene, Toyama, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that plasma levels of 8-epi-prostaglandin F 2␣ (8-epi-PGF 2␣ ), a reliable marker of in vivo oxidative stress, are increased in response to ANG II infusion (2); furthermore, this ANG II-induced increase in plasma 8-epi-PGF 2␣ is inhibited by the treatment with deferoxamine (27), which suggests that iron metabolism is involved in the enhancement of ANG II-induced oxidative stress. In these experiments, however, hydralazine, which did not completely suppress the ANG II-induced upregulation of hepatic TGF-␤1 mRNA upregulation in the current study, also suppressed the ANG II-induced increase in plasma 8-epi-PGF 2␣ levels (2).…”
Section: E Fmentioning
confidence: 99%
“…Direct effect(s) of RAS components on 1␣-hydroxylase or VDR have not been found; however, ANG II reduces renal KLOTHO expression (286,348,443,453), which interferes with FGF23 signaling and results in elevated FGF23 levels (reviewed in Ref. 97).…”
Section: The Klotho-vitamin D-ras Connectionmentioning
confidence: 99%